2022
DOI: 10.3390/ani12162047
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Habitats of Chrysolophus spp. Need Urgent Protection from Habitat Fragmentation in China: Especially Suitable Habitats in Non-Nature Reserve Areas

Abstract: Over the past few years, the wild population of Chrysolophus spp. has decreased remarkably. Habitat fragmentation is a significant cause for this serious threat to the survival of Chrysolophus spp. population. In order to further understand the distribution of potentially suitable habitats of Chrysolophus spp., we used the maximum entropy model to predict the potentially suitable habitats of C. pictus and C. amherstiae in China based on the known distribution. According to the prediction results of the model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A suitable habitat can facilitate the continued existence of a species, and breeding habitats, in particular, are essential for ensuring population reproduction and recovery [3][4][5]. The scientific management of breeding habitats is crucial for species conservation [6][7][8]. Nesting is a very important stage in the life history of birds, and many studies of avian nesting success have examined nesting habitat characteristics and quality [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable habitat can facilitate the continued existence of a species, and breeding habitats, in particular, are essential for ensuring population reproduction and recovery [3][4][5]. The scientific management of breeding habitats is crucial for species conservation [6][7][8]. Nesting is a very important stage in the life history of birds, and many studies of avian nesting success have examined nesting habitat characteristics and quality [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Human-related land-use change, i.e., agricultural expansion and urbanization, is rapidly fragmenting the natural ecosystem and causing biodiversity loss, especially in China [2]. Therefore, habitat fragmentation assessment has become crucial in wildlife protection [3]. However, research showed that the reaction of wildlife habitat to climate change and human influence is species-specific, even for sympatric ones [4,5], indicating the necessity to understand how endangered species react to environmental conditions specifically when designing targeted protection strategy.…”
Section: Introductionmentioning
confidence: 99%